An audit of endocrine dysfunction in children with craniopharyngiomas at Red Cross Children's Hospital and Groote Schuur Hospital from 1976 to 2004 - Omarjee, Zakiyya (Department of Paediatrics and Child Health, 2018)
Background: Craniopharyngiomas account for 6-10% of childhood brain tumours and are the third most common intracranial tumours of childhood. Despite their benign histological appearance, they are often associated with a poor outcome and have significant associated morbidity. Aim: To analyse the data of children with craniopharyngiomas at Red Cross Children's Hospital and Groote Schuur Hospital from 1976 to 2004 with respect to age at presentation, presenting symptoms and preoperative and post-operative endocrine dysfunction. Patients and methods: The records of 45 children aged between 9 months and 13 years were reviewed. The majority of children in the study were aged between 5 and 10 years. There was a considerable delay in the diagnosis in most cases especially in areas outside of Cape Town. Pre-operative tests prior to 2000 were incomplete but have improved since then. Twenty nine percent of our patients had a near total excision of the craniopharyngioma and 29% had partial excisions necessitating adjuvant radiotherapy. The endocrinological, neuro imaging and presenting symptoms were analysed and post-operative tests were reviewed. Where possible neuropsychiatric assessments were accessed as well in order to assess long term neurocognitive deficits Results: The age of presentation of craniopharyngiomas in our group of patients was much younger than in other studies with the largest group of affected children being between 5 and 10 years of age. The most common presenting symptoms in this group were headaches (62%) and visual disturbances (57%). Sixty four percent of the children had preoperative endocrine testing for pituitary dysfunction of which 59% were ACTH and TSH deficient and only 38% were growth hormone deficient. After surgery multiple endocrinopathies were universal with 56% of children having pan hypopituitarism at follow up. There was no reversal of pre-existing hormone deficits after surgery. The management of craniopharyngiomas remains controversial. Twenty nine percent of our patients had a near total excision and 29 % had a partial excision combined with radiotherapy with a further 6 patients receiving intratumoral bleomycin for recurrences. Post operatively the majority of children were on replacement therapy but only 6 patients (14%) received human growth hormone or are receiving human growth hormone currently due to a lack of funds to provide human growth hormone for children with growth hormone deficiency. Seventy percent of the children had central diabetes insipidus post operatively reflecting posterior pituitary damage. Our overall survival rate from 1976 to 2004 was 91 % with a mortality rate of 13%. Most of the deaths were attributed to recurrences of the craniopharyngioma and the complications of bleomycin treatment. Conclusion: Craniopharyngiomas remain tumours associated with significant morbidity. Total excision of the tumour remains a favourable option but the proximity of the craniopharyngioma to the pituitary gland and optic tracts results in devastating sequelae. Although the medical and surgical management of craniopharyngiomas has improved, a significant number of patients had endocrine sequelae. The management of craniopharyngiomas in an African context compares favourably internationally but with limited resources especially with regard to growth hormone replacement, a large proportion of our children are not receiving optimal treatment.